Endomorphisms and automorphisms from subfactors illustrating non-commutative entropy - Svendsen, Anne Louise (Mathematica Scandinavica, 2005)
We present a series of examples of endomorphisms and automorphisms arising from subfactors, which illustrate some of the recent theorems in non-commutative entropy theory. Moreover it is shown that for these examples the Connes-Størmer entropy of the automorphism is maximal and coincides with the topological entropy. This follows from the theorems our examples illustrate, and is also showed directly.